MENINGKATKAN KEMAMPUAN NUMERASI ANAK USIA DINI MELALUI MEDIA KARET GELANG PADA KELOMPOK A DI PAUD NURUL AEINIYAH KARAWANG - Robiah, Siti; Sulaeman, Devi; Riyadi, Ahmad (Penerbit Lafadz Jaya, 2025)
Education has a fundamental role in advancing the development of a nation. In Indonesia, education is mandatory for children from an early age, so every area of child development needs to be stimulated, especially the cognitive aspect through numeracy skills. These skills are crucial in supporting daily activities and preparing children to face the next stage of development. This study used rubber bands as a simple, attractive, and easily accessible tool to improve the numeracy skills of Group A children (aged 4-5 years) at PAUD Nurul Aeiniyah Karawang, which initially had an average of 60%. The study was conducted using the Classroom Action Research (CAR) method initiated by Kurt Lewin in two cycles, through activities that included (1) counting numbers, (2) grouping colors, (3) basic addition and subtraction, and (4) making patterns. The results showed a significant increase, with an average numeracy ability reaching 77% in the second cycle. The greatest increase was found in the indicator of comparing numbers (83%). These findings show that the use of rubber band media is very effective in improving children's numeracy skills because it is concrete, interactive, and appropriate to children's cognitive development stages.